2016
DOI: 10.1371/journal.pone.0163697
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Mitogenic Activity of Recombinant Human Vascular Endothelial Growth Factor VEGF121 Expressed in E. coli Origami B (DE3) with Molecular Chaperones

Abstract: We describe the production of a highly-active mutant VEGF variant, α2-PI1-8-VEGF121, which contains a substrate sequence for factor XIIIa at the aminoterminus designed for incorporation into a fibrin gel. The α2-PI1-8-VEGF121 gene was synthesized, cloned into a pET-32a(+) vector and expressed in Escherichia coli Origami B (DE3) host cells. To increase the protein folding and the solubility, the resulting thioredoxin-α2-PI1-8-VEGF121 fusion protein was co-expressed with recombinant molecular chaperones GroES/EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Disulfide bond formation is a critical step to obtain functional EGF growth factors. Therefore, many strategies have been attempted to overcome this problem, such as utilization of the E. coli Shuffle 30 and Origami 2 (DE3) 31 strains to try to control redox environment, secretion to the periplasm 32 , and fusion with chaperone-proteins, such as oleosin 33 , glutathione S-transferase 34 , SUMO 33 , B1 domain of streptococcal protein G 34 , protein disulfide isomerase (PDI) 35 , N-utilization substance protein A 35 , maltose-binding protein 35 , b'a' domain of PDI (PDIb'a') 35 , ELK16 36 and thioredoxin (Trx) 37 . In general, these studies have demonstrated the requirement of a fusion partner for proper folding of the EGF growth factors, which can be efficiently separated by proteolytic cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide bond formation is a critical step to obtain functional EGF growth factors. Therefore, many strategies have been attempted to overcome this problem, such as utilization of the E. coli Shuffle 30 and Origami 2 (DE3) 31 strains to try to control redox environment, secretion to the periplasm 32 , and fusion with chaperone-proteins, such as oleosin 33 , glutathione S-transferase 34 , SUMO 33 , B1 domain of streptococcal protein G 34 , protein disulfide isomerase (PDI) 35 , N-utilization substance protein A 35 , maltose-binding protein 35 , b'a' domain of PDI (PDIb'a') 35 , ELK16 36 and thioredoxin (Trx) 37 . In general, these studies have demonstrated the requirement of a fusion partner for proper folding of the EGF growth factors, which can be efficiently separated by proteolytic cleavage.…”
Section: Introductionmentioning
confidence: 99%
“…The reason we see a higher cell viability among TIB-HMVECs might be due to increased secretion of VEGF-A, figure 4(c). VEGF is a potent mitogen that regulates endothelial cell proliferation [28,29]. At 7 d, these VEGF values might equilibrate to those similar to MP-HMVECs that we see in figures 3(a) and (d).…”
Section: Effects Of Tib On Cell Viabilitymentioning
confidence: 68%
“…To overcome the mispairing of disulfide bonds, E. coli host strains have been genetically engineered to control the cellular redox environment [ 26 28 ]. As another strategy, solubility enhancers, such as maltose-binding protein (MBP) [ 1 , 17 ], oleosin [ 12 ], low-molecular-weight protamine [ 14 ], HaloTag [ 18 ], glutathione S -transferase [ 1 , 17 ], protein disulfide isomerase (PDI) [ 1 , 17 ], ELK16 [ 29 ], and thioredoxin [ 1 , 17 , 30 ], are fused to the target protein, including GFs. As the solubility of the tag affects the solubility of the passenger protein, choosing an appropriate solubility tag is critical [ 31 ].…”
Section: Introductionmentioning
confidence: 99%